Phosphoenolpyruvate- and ATP-dependent dihydroxyacetone kinases: covalent substrate-binding and kinetic mechanism. - Garcia-Alles, L; Siebold, C; Nyffeler, T; Flükiger-Brühwiler, K; Schneider, P; Bürgi, H; Baumann, U; Erni, B (2004)
Dihydroxyacetone (Dha) kinases are a sequence-conserved family of enzymes, which utilize two different phosphoryldonors, ATP in animals, plants, and some bacteria, and a multiphosphoprotein of the phosphoenolpyruvate carbohydrate phosphotransferase system (PTS) in most bacteria. Here, we compare the PTS-dependent kinase of Escherichia coli and the ATP-dependent kinase of Citrobacter freundii. They display 30% sequence identity. The binding constants of the E. coli kinase for eleven short-chain carbonyl compounds were determined by acetone precipitation of the enzyme-substrate complexes. They are 3.4 microM for Dha, 780 microM for Dha-phosphate (DhaP), 50 microM for D,L-glyceraldehyde (GA), and 90 microM for D,L-glyceraldehyde-3-phosphate. The k(cat) for Dha of the PTS-dependent kinase is 290 min(-1), and that of the ATP-dependent kinase is 1050 min(-1). The Km for Dha of both kinases is <6 microM. The X-ray structures of the enzyme-GA and the enzyme-DhaP complex show that substrates as well as products are bound in hemiaminal linkage to an active-site histidine. Quantum-mechanical calculations offer no indication for activation of the reacting hydroxyl group by the formation of the hemiaminal. However, the formation of the hemiaminal bond allows selection for short-chain carbonyl compounds and discrimination against structurally similar polyols. The Dha kinase remains fully active in the presence of 2 M glycerol, and phosphorylates trace impurities of carbonyl compounds present in glycerol.